Results of the development of a multimodal model of hierarchical structural and functional pathogenetic links of mental disorders due to COVID-19 - Mishiev В’ячеслав; Mikhailov Борис; Grinevich Євгенія; Omelyanovich Віталій; Kuznetsov Ігор (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online.